2005
DOI: 10.1098/rspb.2005.3341
|View full text |Cite
|
Sign up to set email alerts
|

Coprophagy in a cave-adapted salamander; the importance of bat guano examined through nutritional and stable isotope analyses

Abstract: During a two year population ecology study in a cave environment, 15 Eurycea (ZTyphlotriton) spelaea were observed ingesting bat guano. Furthermore, E. spelaea capture numbers increased significantly during the time that grey bats (Myotis grisescens) deposited fresh guano. We investigated the hypothesis that this behaviour was not incidental to the capture of invertebrate prey, but a diet switch to an energy-rich detritus in an oligotrophic environment. Stable isotope assays determined that guano may be assimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 27 publications
0
56
1
Order By: Relevance
“…In subterranean salamanders, the evolution of coprophagy may be an unusual foraging strategy to exploit a nutritious and seasonally abundant resource (i.e., bat guano) in an otherwise food-limited environment. While it has been demonstrated that Grotto salamander larvae will regularly employ coprophagy of calorically-rich bat guano (Fenolio et al 2006), our study suggests that Grotto salamander larvae are unable to thrive on a guano-exclusive diet for a prolonged period. So in this case the coprophagous behavior has emerged in evolution prior to the necessary physiological changes to gain nutrition from it.…”
Section: Discussionmentioning
confidence: 37%
See 4 more Smart Citations
“…In subterranean salamanders, the evolution of coprophagy may be an unusual foraging strategy to exploit a nutritious and seasonally abundant resource (i.e., bat guano) in an otherwise food-limited environment. While it has been demonstrated that Grotto salamander larvae will regularly employ coprophagy of calorically-rich bat guano (Fenolio et al 2006), our study suggests that Grotto salamander larvae are unable to thrive on a guano-exclusive diet for a prolonged period. So in this case the coprophagous behavior has emerged in evolution prior to the necessary physiological changes to gain nutrition from it.…”
Section: Discussionmentioning
confidence: 37%
“…The cave is inhabited by a maternity colony (ca. 15,000 individuals) of federally endangered Gray bats (Myotis grisescens A.H. Howell, 1909) from late April through early November (Fenolio et al 2006(Fenolio et al , 2014. Salamanders were randomly assigned to a negative control group, or one of two prey types and one of four feeding treatments based on percentage of initial body mass: 0% (control) 2.5%, 5%, and 10%.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations